Pengaruh Supporting Electrolyte Pada Penentuan Formaldehida Secara Voltametri Siklik Menggunakan Pencil Lead Electrode (PLE) Modifikasi Lapisan Tipis Perak - Putri, Yunisa Anugrah; Sari, Trisna Kumala; Oktavia, Budhi; Nizar, Umar Kalmar (Periodic, 2024)
Formaldehyde was detected electrochemically using a pencil lead electrode modified with a thin layer of silver (Ag/PLE). Modification of the silver thin layer was carried out by sweeping-potential electrodeposition using the cyclic voltammetry method. This study aims to study the response of PLE and Ag/PLE for determination of formaldehyde and also to determine the optimum conditions of the supporting electrolyte used in the measurement of formaldehyde. The results showed that Ag/PLE provided better performance than PLE and 0.1 M KOH was the optimum supporting electrolyte. Measurement of formaldehyde using Ag/PLE electrodes with a concentration of 10 mM of test analyte. The oxidation peak of formaldehyde is present at a potential of 0.054 Volt.